The Use of Concrete Objects Media to Improve Mathematics Learning Outcomes - Wulandari, Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Learning Mathematics is still a problem for students. This can be seen from the class average score for Mathematics which is lower than the class average for other subjects. The purpose of this classroom action research (CAR) is to find out the improvement of mathematics learning outcomes with concrete media in third grade students of SDN 01 Pageralang Banyumas Regency for the 2019/2020 academic year. In this classroom action research (CAR), it is carried out in 2 cycles. The stages of each cycle are planning, implementation, observation and reflection. In the initial activities of the 22 children, only 8 children or 34.78% had finished studying, while 15 children or 65.21% had not finished learning mathematics, especially the flat field material. From the results of the actions taken, it is proven to be able to increase student learning mastery, namely in the first cycle of 63.7%, it can increase to 95% in the second cycle. The results of this classroom action research indicate that learning with the application of concrete media can improve student learning outcomes in mathematics subjects with completeness reaching 90%.